Age-Dependent Expression of Humanin in the Bull (Bos Taurus) Testis and Its Potential Role in Regulating Hormonal Status, Oxidative Stress and MicroRNA Expression - Louei Monfared, Ali; Rahman Ghyadh, Alaa (The Iraqi Journal of Veterinary Medicine, 2025)
Humanin (HN), a mitochondrial-derived peptide with cytoprotective functions, has not been thoroughly investigated in the bull gonad. This study characterized the developmental localization of HN in the bull testis and its relationship with hormonal status, oxidative stress, and key miRNAs. An age dependent HN expression pattern was seen by immunofluorescence examinations of testicular tissues from pre-pubertal, puberty, mature, and aged bulls. So that, pre-pubertal and aged groups showed faint HN immunoreactivity, pubertal animals showed moderate immunoreactivity, and mature adults showed the most intense immune response (P ≤ 0.0001). In contrast to this, miR-202-5p and miR-21 had their highest expression levels during pre-pubertal, pubertal, and mature testes and a significant decrease in aged bulls (P ≤ 0.0001). Despite the contrasting developmental trends observed at the group level, a correlation analysis involving all individual animals (n = 40) demonstrated a robust positive association between HN and miR-202-5p levels (r = 0.8196, P < 0.001). This finding implies a close regulatory connection between these molecules that functions throughout various developmental stages. Quantitatively, HN levels was correlated positively with serum testosterone (r = 0.5852, P < 0.01) and the antioxidant enzyme SOD (r = 0.8208, P < 0.001), and negatively with the oxidative stress marker MDA (r = - 0.7140, P < 0.001). The current findings show the first developmentally-specific HN expression in the bull testis, which is linked to peak reproductive maturity, hormonal balance, and redox homeostasis. The correlation with miR-202-5p suggests that there is a potential new regulatory network, and that HN is a crucial peptide for testicular function and aging. The results of this study could facilitate additional investigations into the distribution of HN throughout gonadal development, ultimately enhancing the reproductive efficiency of livestock‎‎‎.